2001
DOI: 10.1029/2000jd900778
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous processes involving nitrogenous compounds and Saharan dust inferred from measurements and model calculations

Abstract: Abstract. Experimental data on aerosol chemical composition and gaseous concentrations in various African ecosystems have been obtained under the IGAC DEBITS AFRICA (IDAF)program. In this paper, data covering a complete wet and dry season (1996 and 1998) in the semiarid savanna of the Sahelian region of Niger are presented. The analysis of the aerosol chemical composition and the gas phase concentrations at the Banizoumbou station indicates two strong signatures: a nitrogenous component composed of nitric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 57 publications
(28 reference statements)
0
53
1
Order By: Relevance
“…Such interactions were demonstrated in several field experiments totally or partly dedicated to studies of dust aerosol. Examples include GTE/ABLE 1 (Talbot et al, 1986), ACE-2 (Putaud et al, 2000), IDAF (Galy-Lacaux et al, 2001), MI-NATROC (for nitrate) , TRACE-P (Jordan et al, 2003), SHADE (Formenti et al, 2003). Other measurements also showed sulfate and nitrate enhancements on dust aerosol, at the Puy de Dome (France) (Sellegri et al, 2003), in the Barbados or in East Asia (Mori et al, 2003;Song and Carmichael, 2001).…”
Section: Evolution Of Concentration For Secondary Inorganic Componentsmentioning
confidence: 99%
“…Such interactions were demonstrated in several field experiments totally or partly dedicated to studies of dust aerosol. Examples include GTE/ABLE 1 (Talbot et al, 1986), ACE-2 (Putaud et al, 2000), IDAF (Galy-Lacaux et al, 2001), MI-NATROC (for nitrate) , TRACE-P (Jordan et al, 2003), SHADE (Formenti et al, 2003). Other measurements also showed sulfate and nitrate enhancements on dust aerosol, at the Puy de Dome (France) (Sellegri et al, 2003), in the Barbados or in East Asia (Mori et al, 2003;Song and Carmichael, 2001).…”
Section: Evolution Of Concentration For Secondary Inorganic Componentsmentioning
confidence: 99%
“…HNO 3 , which is extremely soluble in water, is thus easily scavenged by clouds. Galy-Lacaux et al (2001) have demonstrated that heterogenous processes between nitric acid and mineral particles are present all over the African continent.…”
Section: Wet Depositionmentioning
confidence: 99%
“…Within the IDAF framework, several studies of the chemical composition of precipitation representative of African ecosystems have been published. These studies have helped to quantify the wet deposition of biogeochemically important elements and to estimate the contributions of different atmospheric sources (Galy-Lacaux and Modi, 1998;Galy-Lacaux et al, 2001;Sigha et al, 2003;Yoboue et al, 2005;Mphepya et al, 2004Mphepya et al, , 2006Galy-Lacaux et al, 2009). To complement these studies, it is appropriate to study and quantify dry deposition fluxes.…”
Section: Introductionmentioning
confidence: 99%